2019
DOI: 10.1021/acsomega.9b00251
|View full text |Cite
|
Sign up to set email alerts
|

Polyelectrolyte vs Polyampholyte Behavior of Composite Chitosan/Gelatin Films

Abstract: Composite films of proteins and polysaccharides have a broad range of biomedical and food packaging applications, in which they are frequently exposed to fluid environments with varying ionic strengths. In the present work, we report the behavior of biopolymer films derived from chitosan (Ch), gelatin (GEL), and Ch/GEL mixture in salt solutions with varying concentrations and ion charges. The swelling and dissolution of the Ch films reduced with increasing salt concentration due to the polyelectrolyte behavior… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 42 publications
0
10
0
Order By: Relevance
“…Benbettaieb et al found that preparation at a pH = 5.5 between the pI of gelatine (pI = 4.5) and pKa of chitosan (pKa = 6.2–6.5) permits to generate the maximum amount of electrostatic interactions (Benbettaieb et al ., 2020). Another group believed that gelatine containing amino acids with positive (amine) and negative (carboxyl) ionisable groups behaved as a polyampholyte, while chitosan was a copolymer of glucosamine (containing ionisable amine groups) and n ‐acetyl glucosamine, and therefore behaved as a polyelectrolyte (Pinto Ramos, Sarjinsky, Alizadehgiashi, Mobus, & Kumacheva, 2019). After blending, the formation of polyelectrolyte complexes occurred through electrostatic interaction, thus forming the complex.…”
Section: Affecting Factorsmentioning
confidence: 99%
See 2 more Smart Citations
“…Benbettaieb et al found that preparation at a pH = 5.5 between the pI of gelatine (pI = 4.5) and pKa of chitosan (pKa = 6.2–6.5) permits to generate the maximum amount of electrostatic interactions (Benbettaieb et al ., 2020). Another group believed that gelatine containing amino acids with positive (amine) and negative (carboxyl) ionisable groups behaved as a polyampholyte, while chitosan was a copolymer of glucosamine (containing ionisable amine groups) and n ‐acetyl glucosamine, and therefore behaved as a polyelectrolyte (Pinto Ramos, Sarjinsky, Alizadehgiashi, Mobus, & Kumacheva, 2019). After blending, the formation of polyelectrolyte complexes occurred through electrostatic interaction, thus forming the complex.…”
Section: Affecting Factorsmentioning
confidence: 99%
“…As for films, gelatine displayed a polyampholyte behaviour in which swelling and dissolution were enhanced in salt solutions due to the weaker ionic cross‐linking between the charged amine and carboxyl groups and attraction between COO‐ and NH 3 + groups of gelatine being screened in NaCl solutions, resulting in expansion of polymer network (Pinto Ramos et al ., 2019). The swelling and dissolution of the chitosan films was reduced with increasing NaCl concentration due to the polyelectrolyte behaviour of this biopolymer, in which ionic repulsion between NH 3 + groups of chitosan was screened, resulting in contraction of polymer network.…”
Section: Affecting Factorsmentioning
confidence: 99%
See 1 more Smart Citation
“…; however, the final properties displayed can differ according to the manipulation applied. For instance, polyampholytes typically present enhanced swelling and dissolution due to screened interactions compared to PEs of the same subunits that prepare the gel in the conventional way [ 30 , 31 ]. In contrast, zwitterionic PE gels are recognised as having a charge density that is neutrally charged.…”
Section: Fundamentals Of Pe Gelsmentioning
confidence: 99%
“…22 For gelatin at all the studied concentrations the trend is similar; that is, an increase in NaCl concentration resulted in a decrease of z potential which can be attributed to the fact that an increasing ionic strength of salt solutions results in screened attraction between ionized carboxyl and amine groups. 23 The experimental conditions selected for the formation of ChS-gelatin PECs are highlighted in purple in Fig. 2 and summarized in Table 1.…”
Section: Paper Materials Advancesmentioning
confidence: 99%